Indigenous cattle biodiversity in India: Adaptation and conservation - Sarang, Sujith Kumar; Sreekumar, Damodaran; Sejian, Veerasamy (Reproduction and breeding, 2024)
Indigenous breeds of cattle are suitable for varying climatic conditions of the tropical environment by virtue of a series of species-specific traits and adaptive strategies. Such traits and adaptive strategies could be generally classed into morphological/anatomical, physiological, behavioural, neuro-endocrine, haematological, and molecular and cellular features. At the same time, over the years it is found that the population of indigenous cattle is decreasing at a faster rate all over the world. This is mainly due to the preponderance of crosses of indigenous cattle with exotic/temperate high producing cattle for improved milk production. As a result, if suitable measures are not taken for conserving indigenous breeds of cattle, the diversity will go down drastically and may at one stage become highly endangered in status. For working out conservation plans and breeding strategies, the fundamental requirements include genetic characterization by means of gene and microsatellite markers along with evaluation of genetic variability, population structure and composition. Conserving the diversity of indigenous germplasm will help to choose breeds of cattle that adapt to changing climatic environment. Such an approach could help in formulating strategies for conservation and breeding plans and further could also lay the foundation for effective utilisation of indigenous cattle under different production systems. •Indigenous cattle population is decreasing at a faster rate all over the world.•More sustainable methods are required for conservation of indigenous cattle breeds.•Optimum utilization of cattle biodiversity is required for sustainable food production.•Advanced biotechnological tools can identify climate resilient cattle breeds.